Optimization of process conditions for high cell density proliferation of DF-1 cells in bioreactor - Mel, Maizirwan; Arifin, Mohd Azmir; Sohif, Hajar Naemah; Syed Hasan, Sharifah (Malaysian Medical Associations, 2010)
The purpose of this study was to optimize agitation speed, microcarrier concentration and pO2 levels in bioreactor for culturing DF-1cells in DMEM media supplemented with 7% fetal bovine serum. Statistical analysis has shown that the model derived from the results was proven to be significant and pO2 level turned out as the most significant parameter in the experiment. As predicted by analysis, cells grew up to 1.190 x 106 cells/ml when moderate agitation speed, microcarrier concentration, and pO2 level are applied.